Coronary artery bypass graft surgery with bilateral internal mammary artery. Medium-term results - Castillo, Julio (2020)
Introduction: Coronary artery bypass graft (CABG) surgery is one of the main strategies in the treatment of coronary heart disease. The benefit of using the left internal mammary artery (IMA) to revascularize the anterior descending artery is greatly demonstrated, improving long-term survival in patientsreceiving this graft. On the other hand there are variable currents about the use of two internal mammary arteries, although several studies have already demonstrated the superiority of the use of two mammary arteries over one. Methodology: Retrospective study of Coronary artery bypass graft surgeries with bilateral mammary artery, performed at Instituto Nacional Cardiovascular - INCOR EsSalud between January 2012 and June 2018. The objective was to determine the mortality rate and major adverse cardiovascular events in a medium term follow-up of 30 months. Results: 121 patients were operated with bilateral internal mammary artery. All patients underwent dissection of mammary artery with skeletonized technique. There was one in-hospital death due tomediastinitis. Major adverse cardiovascular events occurred in 5.8% of patients (death 0.8%, stroke 0%, perioperative myocardial infarction 1.6%, need for new coronary intervention 3.3%). The incidence of mediastinitis and/or sternal reconstruction was 0.8%. Conclusions: CABG with bilateral IMA is a safe procedure, with low mortality rates and low major adverse cardiovascular events in a 30-month follow-up.